Effect of Topical Propranolol Gel on Plasma Renin,Angiotensin Ⅱ and Vascular Endothelial Growth Factor in Superficial Infantile Hemangiomas - 唐玉娟 张再重 陈少全 陈淑明 黎成金 陈剑伟 原博 夏印 王烈 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
The effect of topical propranolol gel on the levels of plasma renin,angiotensin Ⅱ（ATⅡ） and vascular endothelial growth factor（VEGF） in superficial infantile hemangiomas（IHs） was investigated. Thirty-three consecutive children with superficial IHs were observed pre-treatment,1 and 3 months after application of topical propranolol gel for the levels of plasma renin,AT Ⅱand VEGF in Department of General Surgery of Dongfang Hospital from February 2013 to February 2014. The plasma results of IHs were compared with those of 30 healthy infants of the same age from out-patient department. The clinical efficiency of topical propranolol gel at 1st,and 3rd month after application was 45%,and 82% respectively. The levels of plasma renin,AT and VEGF in patients preⅡ-treatment were higher than those in healthy infants（565.86±49.66 vs. 18.19±3.56,3.20±0.39 vs 0.30±0.03,and 362.16±27.29 vs. 85.63±8.14,P〈0.05）. The concentrations of VEGF and renin at 1st and 3rd month after treatment were decreased obviously as compared with those pre-treatment（271.51±18.59 vs. 362.16±27.29,and 405.18±42.52 vs. 565.86±49.66 P〈0.05; 240.80±19.89 vs. 362.16±27.29,and 325.90±35.78 vs. 565.86±49.66,P〈0.05,respectively）,but the levels of plasma AT declined slightly Ⅱ（2.96±0.37 vs. 3.20±0.39,and 2.47±0.27 vs. 3.20±0.39,P〉0.05）. It was indicated that the increased renin,AT Ⅱand VEGF might play a role in the onset or development of IHs. Propranolol gel may suppress the proliferation of IHs by reducing VEGF.